Effect of seed generation, rhizobia inoculation and plant density on productivity and seed quality of soybean [Glycine max (l.) Merril] and groundnut [Arachis hypogea (l.)] In Dedza and Machinga districts of Malawi - Kalumba, Jester (Lilongwe University of Agriculture and Natural Resources, 2021)
Two on-farm, researcher designed-farmer managed trials were arranged in split-plot in a randomised complete block design (RCBD) with seed generation as main plot factor while inoculation and plant density were subplot factors for soybean and groundnut trials, respectively, in Dedza and Machinga districts in the 2017/2018 season. Following the field trials, Screen house experiments were conducted at Bunda College, Crop and Soil Sciences Students research farm to evaluate the effect of mother environment on seed quality of soybean and groundnut. This study was laid out in a completely randomised design (CRD). The overall objective of these trials was to investigate effects of seed generation, inoculation, plant density and mother environment on soybean and groundnut productivity and seed quality. In Machinga, response to inoculation for BNF and grain yield of soybean was 67 % (p=0.002) and 27 % (p=0.016) higher in recycled than certified seed, respectively. In Dedza inoculation of soybean significantly increased BNF by 74 % (p=0.004) and grain yield by 21 % (p=0.029), while planting certified soybean increased grain yield by 18 % (p=0.031). In Dedza, planting recycled seed significantly increased BNF by 21.4 % (p=0.011) and grain yield by 24.2 % (p=0.041) while planting groundnut in twin rows increased BNF by 38.5 % (p=0.004) and grain yield by 145.8 % (p<0.001), respectively. In Machinga, planting groundnut in twin rows increased BNF by 32.5 % (p=0.025) and grain yield by 87 % (p<0.001). Because of poor germination for certified groundnut seed, a covariate analysis controlling for plant density revealed that use of certified seed increased BNF and yield of groundnut (p<0.001). Results of screen house experiments showed that mother environment significantly affected seed quality for both soybean and groundnut indicating that seed production site is an important element for production of quality seed.